Optimal echo times for multi‐gradient echo‐based B0 field‐mapping. (27th April 2020) - Geiger, Yasmin; Tal, Assaf
Abstract : B0 field maps are used ubiquitously in neuroimaging, in disciplines ranging from magnetic resonance spectroscopy to temperature mapping and susceptibility‐weighted imaging. Most B0 maps are acquired using standard gradient‐echo–based vendor‐provided sequences, often comprised of two echoes spaced a few milliseconds apart. Herein, we analyze the optimal spacing of echo times, defined as those maximizing precision—minimizing the standard deviation—for a fixed total acquisition time. Field estimation is carried out using a weighted least squares estimator. The standard deviation is shown to be approximately inversely proportional to the total acquisition time, suggesting a law of diminishing returns, whereby substantial gains are obtained up to a certain point, with little improvement beyond that point. Validations are provided in a phantom and a group of volunteers. Multi‐gradient echo sequences are readily available on all manufacturer platforms, making our recommendations straightforward to implement on any modern scanner. Abstract : We derive the echo times for multi‐gradient echo field‐mapping sequences that minimize the noise in the field maps for a given total acquisition time. We show that the noise decreases approximately as the inverse of the total acquisition time, showing that, initially, large gains to precision can be achieved by relatively small increases to the total acquisition time. Conversely, beyond a certain point, however, additional acquisition time leads to small improvements in precision.